Cal. Stat. 156, §153 - (:unkn) unknown (General Publisher, 1883)
All taxes and fines received from licenses related to the storage, manufacture, and sale of gunpowder, and other explosive materials shall be collected into a "Fireman's Charitable Fund."
--
Keywords: GUN POWDER STORAGE